-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathgradient_d.jl
189 lines (150 loc) · 6.23 KB
/
gradient_d.jl
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
function ∂x(s, dx, mf, i, j, k)
ret = (s[i+1,j,k] - s[i-1,j,k])/2/dx * mf[i,j]
end
function ∂y(s, dy, mf, i, j, k)
ret = (s[i,j+1,k] - s[i,j-1,k])/2/dy * mf[i,j]
end
function ∇(s, dx, dy, mf, i, j, k)
ret = (∂x(s, dx, mf, i, j, k), ∂y(s,dy,mf, i, j, k))
end
function ∇div(va, vb, dx, dy, mf, i, j, k)
dudx = ∂x(va, dx, mf, i, j, k)
dvdy = ∂y(vb, dy, mf, i, j, k)
return dudx + dvdy
end
function ∂π(s, h, i, j, k)
ret = (h[k-1]^2 * s[i,j,k+1] - h[k]^2 * s[i,j,k-1]) / (h[k]*h[k-1]* (h[k] + h[k-1])) - s[i,j,k]*(h[k-1]-h[k])/(h[k]*h[k-1])
end
# 2nd order derivatives
function ∂²x(s, dx2, mf2, i, j, k)
ret = (s[i+1,j,k] + s[i-1,j,k] - 2*s[i,j,k])/dx2 * mf2[i,j]
end
function ∂²y(s, dy2, mf2, i, j, k)
ret = (s[i,j+1,k] + s[i,j-1,k] - 2*s[i,j,k])/dy2 * mf2[i,j]
end
function ∇²(s, dx2, dy2, mf2, i, j, k)
ret = (s[i,j+1,k]+s[i,j-1,k]+s[i+1,j,k]+s[i-1,j,k]- 4*s[i,j,k])/dx2 * mf2[i,j]
end
function ∂²π(s, h, i, j, k)
ret = 2/h[k]/h[k-1]*( (h[k-1]*s[i,j,k+1] + h[k]*s[i,j,k-1]) / (h[k]+h[k-1]) - s[i,j,k])
end
function diff2nd(ap1, am1, da, mfij)
ret = (ap1 - am1) /2/da * mfij
end
function ∂xy(s, dx, dy, mf2, i, j, k)
ret = mf2[i,j]/(4*dx*dy) * ( s[i+1,j+1,k] + s[i-1,j-1,k] - s[i+1,j-1,k] - s[i-1,j+1,k])
end
function ∂xπ(s, dx, h, mf, i, j, k)
dπjm1 = ∂π(s, h, i-1, j, k)
dπjp1 = ∂π(s, h, i+1, j, k)
ret = diff2nd(dπjp1, dπjm1, dx, mf[i,j])
end
function ∂yπ(s, dy, h, mf, i, j, k)
dπjm1 = ∂π(s, h, i, j-1, k)
dπjp1 = ∂π(s, h, i, j+1, k)
ret = diff2nd(dπjp1, dπjm1, dy, mf[i,j])
end
function ∇f∇dis(s, dx, dy, mf, mf2, f, fx, fy, i, j, k)
sx , sy = ∇(s, dx, dy, mf, i, j, k)
∇f∇t = fx[i,j]*sx + fy[i,j]*sy + f[i,j]*∇²(s, dx^2, dy^2, mf2, i, j, k)
end
# 3rd order derivatives
"""i = 2:nx-1, j = 2:ny-1
∂³x(s, dx3, mf3, i, j, k)"""
function ∂³x(s, dx3, mf3, i, j, k)
ret = (s[i+2,j,k] - 2*s[i+1,j,k] + 2*s[i-1,j,k] - s[i-2,j,k])/2/dx3 * mf3[i,j]
end
"""i = 2:nx-1, j = 2:ny-1
∂³y(s, dy3, mf3, i, j, k)"""
function ∂³y(s, dy3, mf3, i, j, k)
ret = (s[i,j+2,k] - 2*s[i,j+1,k] + 2*s[i,j-1,k] - s[i,j-2,k])/2/dy3 * mf3[i,j]
end
function ∂³xy2(s, dx, dy2, mf3, i, j, k)
ret = (s[i+1,j+1,k] + s[i+1,j-1,k] - 2*s[i+1,j,k] - s[i-1,j+1,k] - s[i-1,j-1,k] + 2*s[i-1,j,k])/2/dy2/dx * mf3[i,j]
end
function ∂³x2y(s, dx2, dy, mf3, i, j, k)
ret = (s[i+1,j+1,k] + s[i-1,j+1,k] - 2*s[i,j+1,k] - s[i+1,j-1,k] - s[i-1,j-1,k] + 2*s[i,j-1,k])/2/dy/dx2 * mf3[i,j]
end
# 4th order derivatives
"""i = 2:nx-1, j = 2:ny-1
∇⁴(s, dx2, dy2, mf2, i, j, k) """
function ∇⁴(s, dx2, dy2, mf2, i, j, k)
ret = (s[i,j+2,k]+s[i,j-2,k]+s[i+2,j,k]+s[i-2,j,k] - 8*(s[i,j+1,k]+s[i,j-1,k]+s[i+1,j,k]+s[i-1,j,k]) + 2*(s[i+1,j+1,k]+s[i-1,j+1,k]+s[i+1,j-1,k]+s[i-1,j-1,k]) + 20*s[i,j,k])/(dx2^2) * mf2[i,j]^2
end
function ∂⁴x3π(s, dx3, h, mf3, i, j, k)
dx3kp1 = ∂³x(s, dx3, mf3, i, j, k+1)
dx3k = ∂³x(s, dx3, mf3, i, j, k)
dx3km1 = ∂³x(s, dx3, mf3, i, j, k-1)
ret = (h[k-1]^2 * dx3kp1 - h[k]^2 * dx3km1) / (h[k]*h[k-1]* (h[k] + h[k-1])) - dx3k*(h[k-1]-h[k])/(h[k]*h[k-1])
end
function ∂⁴y3π(s, dy3, h, mf3, i, j, k)
dy3kp1 = ∂³y(s, dy3, mf3, i, j, k+1)
dy3k = ∂³y(s, dy3, mf3, i, j, k)
dy3km1 = ∂³y(s, dy3, mf3, i, j, k-1)
ret = (h[k-1]^2 * dy3kp1 - h[k]^2 * dy3km1) / (h[k]*h[k-1]* (h[k] + h[k-1])) - dy3k*(h[k-1]-h[k])/(h[k]*h[k-1])
end
function ∂⁴x2π2(s, dx2, h, mf2, i, j, k)
dx2kp1 = ∂²x(s, dx2, mf2, i, j, k+1)
dx2k = ∂²x(s, dx2, mf2, i, j, k)
dx2km1 = ∂²x(s, dx2, mf2, i, j, k-1)
ret = 2/h[k]/h[k-1]*( (h[k-1]*dx2kp1 + h[k]*dx2km1) / (h[k]+h[k-1]) - dx2k)
end
function ∂⁴y2π2(s, dy2, h, mf2, i, j, k)
dy2kp1 = ∂²y(s, dy2, mf2, i, j, k+1)
dy2k = ∂²y(s, dy2, mf2, i, j, k)
dy2km1 = ∂²y(s, dy2, mf2, i, j, k-1)
ret = 2/h[k]/h[k-1]*( (h[k-1]*dy2kp1 + h[k]*dy2km1) / (h[k]+h[k-1]) - dy2k)
end
function ∂⁴xy2π(s, dx, dy2, h, mf3, i, j, k)
dxy2kp1 = ∂³xy2(s, dx, dy2, mf3, i, j, k+1)
dxy2k = ∂³xy2(s, dx, dy2, mf3, i, j, k)
dxy2km1 = ∂³xy2(s, dx, dy2, mf3, i, j, k-1)
ret = 2/h[k]/h[k-1]*( (h[k-1]*dxy2kp1 + h[k]*dxy2km1) / (h[k]+h[k-1]) - dxy2k)
end
function ∂⁴x2yπ(s, dx2, dy, h, mf3, i, j, k)
dx2ykp1 = ∂³x2y(s, dx2, dy, mf3, i, j, k+1)
dx2yk = ∂³x2y(s, dx2, dy, mf3, i, j, k)
dx2ykm1 = ∂³x2y(s, dx2, dy, mf3, i, j, k-1)
ret = 2/h[k]/h[k-1]*( (h[k-1]*dx2ykp1 + h[k]*dx2ykm1) / (h[k]+h[k-1]) - dx2yk)
end
"""i = 2:nx-1, j = 2:ny-1
∇f∇∂ππ(s, dx, dy, h, mf, mf2, f, fx, fy, i, j, k)"""
function ∇f∇∂ππ(s, dx, dx2, dy, h, mf, mf2, f, fx, fy, i, j, k)
pij = ∂²π(s, h, i, j, k)
pijp1 = ∂²π(s, h, i, j+1, k)
pijm1 = ∂²π(s, h, i, j-1, k)
pip1j = ∂²π(s, h, i+1, j, k)
pim1j = ∂²π(s, h, i-1, j, k)
px = (pip1j - pim1j)/2/dx * mf[i,j]
py = (pijp1 - pijm1)/2/dy * mf[i,j]
delp = (pijp1+pijm1+pip1j+pim1j-4*pij)/dx2 * mf2[i,j]
ret = fx[i,j]*px + fy[i,j]*py + f[i,j]*delp
end
"""i = 3:nx-2, j = 3:ny-2
∇f∇∂xπ(s, dx, dy, h, mf, mf2, f, fx, fy, i, j, k) """
function ∇f∇∂xπ(s, dx, dx2, dy, h, mf, mf2, f, fx, fy, i, j, k)
pij = ∂xπ(s, dx, h, mf, i, j, k)
pijp1 = ∂xπ(s, dx, h, mf, i, j+1, k)
pijm1 = ∂xπ(s, dx, h, mf, i, j-1, k)
pip1j = ∂xπ(s, dx, h, mf, i+1, j, k)
pim1j = ∂xπ(s, dx, h, mf, i-1, j, k)
px = (pip1j - pim1j)/2/dx * mf[i,j]
py = (pijp1 - pijm1)/2/dy * mf[i,j]
delp = (pijp1+pijm1+pip1j+pim1j-4*pij)/dx2 * mf2[i,j]
delfdelxπ = fx[i,j]*px + fy[i,j]*py + f[i,j]*delp
return delfdelxπ, delp
end
"""i = 3:nx-2, j = 3:ny-2
∇f∇∂yπ(s, dx, dy, h, mf, mf2, f, fx, fy, i, j, k)"""
function ∇f∇∂yπ(s, dx, dy, dy2, h, mf, mf2, f, fx, fy, i, j, k)
pij = ∂yπ(s, dy, h, mf, i, j, k)
pijm1 = ∂yπ(s, dy, h, mf, i, j-1, k)
pijp1 = ∂yπ(s, dy, h, mf, i, j+1, k)
pip1j = ∂yπ(s, dy, h, mf, i+1, j, k)
pim1j = ∂yπ(s, dy, h, mf, i-1, j, k)
px = (pip1j - pim1j)/2/dx * mf[i,j]
py = (pijp1 - pijm1)/2/dy * mf[i,j]
delp = (pijp1+pijm1+pip1j+pim1j-4*pij)/dy2 * mf2[i,j]
delfdelyπ = fx[i,j]*px + fy[i,j]*py + f[i,j]*delp
return delfdelyπ, delp
end